Nerve conduction parameters in children with severe acute malnutrition treated with standard nutritional therapy - Khalid, Naman; Dewi, Msy Rita; Indra, RM; Anzar, Julius; Nova, Ria; Indrayadi, Indrayadi; Hasanah, Yulisnawati; Fauzi, Moretta Damayanti (Paediatrica Indonesiana, 2025)
Background Nerve damage has been found in malnourished patients due to deficiencies in micronutrients and macronutrients. Studies on nerve conduction in malnourished children are scarce, specifically those comparing nerve conduction parameters before and after nutritional intervention, are few. Objective To identify nerve conduction changes in children with severe acute malnutrition (SAM) treated with standard nutritional therapy. Methods This was a one-group pretest-posttest quasi-experimental study on children with SAM aged 1 month to 18 years who received standard nutritional therapy for 3 months. We recorded anthropometric data and measured motor and sensory nerve conduction velocity (NCV) of the upper and lower limb nerves before and after the nutritional intervention. Results Thirty participants were included in the study; only 27 underwent post-treatment follow-up nerve conduction testing. All anthropometric indices increased after the intervention, except for body length/height. Moderate correlations were observed between pre-intervention weight and NCVs of the right sural sensory (r=0.496; P=0.005) and left median motor (r=-0.502; P=0.024) nerves. After intervention, conduction velocities of the left median sensory nerve (r=0.750; P=<0.001), right median motor nerves (r=0.521; P=0.015), left ulnar motor nerves (r=0.628; P=0.005), and left tibial motor nerves (r=0.419; P=0.047), had moderate to strong correlations with weight. There were moderate post-treatment correlations between BMI and NCV in the right ulnar (r=0.534; P=0.013) and right fibular (r=0.441; P=0.031) motor NCVs. Conclusion There are significant correlations between weight and some motor and sensory NCVs, as well as between BMI and motor NCVs, after 3 months of receiving nutritional therapy.